2021
DOI: 10.3390/ijms22137127
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Palmitic Acid Augmentation in COVID-19 Pathologies

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has claimed over 2.7 million lives globally. Obesity has been associated with increased severity and mortality of COVID-19. However, the molecular mechanisms by which obesity exacerbates COVID-19 pathologies are not well-defined. The levels of free fatty acids (FFAs) are elevated in obese subjects. This study was therefore designed to examine how excess levels of different FFAs may affect the progression of COVID-19. Biological molecules associated with palmitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Additionally, some lightgreen module hub-high traffic genes, including GLUL ( 268 ), ACSL1 ( 269 ), TRIB1 ( 236 ), TUBA1B ( 270 ), PLEK ( 271 , 272 ), HSPA5 ( 273 , 274 ), and IRAK3 ( 275 ) may contribute to the pathogenesis of COVID-19. For example, SARS-CoV-2 spikes can drive the infection process of host cells by binding to cell-surface heat shock protein A5 ( HSPA5 ) receptor ( 273 , 276 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some lightgreen module hub-high traffic genes, including GLUL ( 268 ), ACSL1 ( 269 ), TRIB1 ( 236 ), TUBA1B ( 270 ), PLEK ( 271 , 272 ), HSPA5 ( 273 , 274 ), and IRAK3 ( 275 ) may contribute to the pathogenesis of COVID-19. For example, SARS-CoV-2 spikes can drive the infection process of host cells by binding to cell-surface heat shock protein A5 ( HSPA5 ) receptor ( 273 , 276 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other hub-high traffic genes in this module, such as BTAF1 ( 216 ), EZH2 ( 346 ), NPM1 ( 347 ), TPT1 ( 151 , 269 , 348 ), LDHA ( 217 , 268 ), PTPRC ( 189 ), SOS1 ( 349 , 350 ), DDX5 ( 351 , 352 ), BCL10 ( 162 , 353 ), EEF1B2 ( 354 ), CALM1 ( 344 ), EIF4A2 , EIF4B ( 336 , 355 , 356 ), EEF1A1 ( 269 , 354 ), HNRNPA1 ( 228 , 347 ), and IFNG ( 8 , 357 , 358 ), have important roles in development/inhibition of COVID-19. Overexpression of SARS-CoV-2 ORF6 caused HNRNPA1 nuclear accumulation, subverting the host mRNA export system and reducing nucleus size ( 359 ).…”
Section: Discussionmentioning
confidence: 99%
“…The proinflammatory cytokines and chemokines, such as IL‐6, IL‐8, tumour necrosis factor (TNF), IL‐17, IL‐12, IL‐1, IP‐10, MCP‐1, and CCL5, were generally increased with higher BMI. 27 , 28 , 36 , 40 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 Furthermore, high levels of IL‐10, an anti‐inflammatory cytokine, appear to be a hallmark of hyperinflammation during severe SARS‐CoV‐2 infection, 57 , 58 and some studies included in this review observed that IL‐10 levels predict poor outcomes in COVID‐19 patients with obesity. 32 , 51 In an attempt to reduce the high COVID‐19 mortality rates due to a cytokine storm, intensive research is underway examining the use of anti‐inflammatory drugs.…”
Section: Resultsmentioning
confidence: 87%
“…36 Increase in the level of palmitic acid has been correlated with inflammatory mediation and increased apoptotic events, being associated with worse outcomes in COVID-19 patients. 37 Higher levels of 4hydroxy-2-nonenal-glutathione in deceased patients may indicate enhanced levels of reactive oxygen species (ROS). Sulfate (SO 3 − ) and iduronic acid (IdoA) may partially result from the glycosaminoglycan dermatan sulfate degradation, which has been associated with the SARS-CoV-2 infection 38 both through the virus' direct effect on tissues and indirectly through inflammatory processes.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Thus, higher levels of this metabolite can be associated with oxidative damage. , Furthermore, SARS-CoV-2 is able to recruit biliverdin at the level of the spike protein via allostery, dampening the binding with neutralizing antibodies and leading to the worsening of the clinical condition of COVID-19 patients . Increase in the level of palmitic acid has been correlated with inflammatory mediation and increased apoptotic events, being associated with worse outcomes in COVID-19 patients . Higher levels of 4-hydroxy-2-nonenal-glutathione in deceased patients may indicate enhanced levels of reactive oxygen species (ROS).…”
Section: Resultsmentioning
confidence: 99%